Pengelolaan Kelas pada Pembelajaran Puisi Rakyat (Pantun) Menggunakan Model Problem Based Learning (PBL) dalam Kurikulum Merdeka di SMP Negeri 11 Kota Bengkulu - Suciawati, Agilia Rahma; Utomo, Padi; Kurniawan, Rio (UNIB Press, 2025)
The Problem Based Learning model is an innovative and participatory learning model in the Independent Curriculum which emphasizes solving real problems to increase student involvement and learning effectiveness. The purpose of this study is to describe how the Problem Based Learning approach is used to manage folk poetry learning courses (pantun) in the autonomous curriculum of SMPN 11 Bengkulu City. This type of research is qualitative and uses a descriptive method. The data in this study is the management of folk poetry (pantun) learning class activities carried out by Indonesian teachers in class VII H at SMPN 11 Bengkulu City. The data sources are teachers and students in Indonesian learning for grade VIIH students at SMPN 11 Bengkulu City. The data collection method was carried out through interviews, documentation, video recording, and observation. In this study, the data analysis technique was carried out using the steps of recording while observing the teacher who was teaching, recording evidence of activities related to the problem being studied, analyzing data, analysing data, clarifying data, interpreting data and drawing conclusions. The results of the study show that the management of folk poetry learning classes (pantun) using the Promblem Based Learning model in the independent curriculum at SMPN 11 Bengkulu City related to Problem Based Learning has been carried out using Problem Based Learning syntax such as orientation, regulating students, supervising individual and group research, presenting discussion findings, and assessing and analyzing the problem-solving process. Classroom management is demonstrated by the way the instructor organizes the class and creates a welcoming environment for learning. Students' responses to questions, group study sessions, and participation in completing assignments given by teachers are indicators of their level of learning engagement.